EDUCATION AS A TOOL FOR CULTURAL DIALOGUE - Smetanová, Eva (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
In a contemporary world, which is multicultural and interconnected, intercultural dialogue is essential for fostering mutual understanding and social cohesion. Education plays a vital role in promoting this dialogue by equipping individuals with the cultural awareness, critical thinking, and communication skills necessary for constructive engagement. By integrating intercultural learning across various educational levels, societies can counter prejudice, reduce conflict, and build inclusive communities.
Keywords: intercultural dialogue; education; cultural awareness; media literacy; global citizenship